Polysyncraton (Ascidiacea, Didemnidae): a re-examination of some specimens and descriptions of three new species - Oliveira, L. M.; Hoeksema, B. W.; Rocha, R. M. (European Journal of Taxonomy, 2019)
Polysyncraton Nott, 1892 is the second largest genus of didemnid ascidians; it has a wide distribution ranging from temperate to tropical waters. Seventy-one specimens of Polysyncraton from eight museum collections and recently collected samples were analyzed. This resulted in the description of three new species (P. cabofriense Oliveira & Rocha sp. nov. from Brazil, P. globosum Oliveira & Rocha sp. nov. from Australia and P. snelliusi Oliveira & Rocha sp. nov. from Suriname) and emended descriptions of three further species (P. amethysteum (Van Name, 1902), P. magnilarvum (Millar, 1962) and P. purou C. Monniot & F. Monniot, 1987).